Spread of hoof pathology in donkeys in the Central and Eastern regions of Ukraine - Kyrychko, B.; Sakharova, O. (Scientific Progress & Innovations, 2022)
Hoof pathologies in donkeys are quite an actual problem in the countries of the world, where they are comprehensively studied. For a long period of time in Ukraine, veterinary scientists did not pay enough attention to hoof diseases in donkeys, despite the rather high interest in keeping donkeys as productive and working animals, as well as pets. Indicators of the spread of hoof pathologies in donkeys have their differences in different countries of the world, which affect the specifics of their diagnosis, treatment and prevention. Therefore, today the need to study the spread of donkey hoof pathologies in the regions of Ukraine is obvious. Our research on this issue has shown that hoof pathologies in donkeys older than one year in the central and eastern regions of Ukraine are quite widespread and account for 53.8 % of all diseases and are manifested in 90 % of the studied animals. During the examination of donkeys, various postural defects of the limbs were found in most of the examined animals (70.1 %), which have a direct impact on the development of hoof pathologies. We divided all registered hoove pathologies of donkeys into three groups: hoove pathologies of the inflammatory type, hoove pathologies of the non-inflammatory type and onchymycosis (superficial suppuration) of the hooves. 48% of all recorded hoof pathologies in the examined donkeys are non-inflammatory hoof pathologies, among which the largest part (12.7 %) is occupied by overgrown hooves, which were detected in 61.3 % of animals. Hoof imbalance was registered in more than 80 % of the examined donkeys. Medio-lateral hoof imbalance occurred in 41.3 % of donkeys, dorso-palmar imbalance in 46.3 %. Among other non-inflammatory hoof pathologies were straight and sharp hoof, contracture of the superficial digital flexor, hypoflexion of the flexors, oblique hoof, deformity and distortion of the hoof, frog dystrophy, etc. Among the hoof pathologies of the inflammatory type, aseptic pododermatitis (59.4 %), white line induration (43.8 %) and chronic laminitis (25.0 %) were most often recorded. Hoof onychomycosis was registered in 80% of the studied animals, which accounted for 24 % of all recorded hoof pathologies. As it turned out, the hoof frog is first affected, then the white line (white line disease), then the process can move to the hoof wall (seedy toe).